Genetic algorithms based optimal fuzzy logic control system design - Qi, Xiaoming (2009)
The goal of this thesis is to develop systematic design methodologies for fuzzy logic controller (FLC) using genetic algorithms (GAs). Main subjects are how to systematize the fuzzy logic controller design procedure and how to embed the genetic algorithms with the control objectives or performance criteria.